therefore
Bottle 3
vanilla=1 1/2
almond=4 1/2
pineapple=6Part 1) Bottle 1 (vanilla=1,almond=3,pineapple=4)
Part 2) Bottle 2 (vanilla=2,almond=6,pineapple=8)
Part 3) Bottle 3 (vanilla=1 1/2,almond=4 1/2,pineapple=6)
Explanation:
Let
x ----> the amount of vanilla sent
y ----> amount of almond sent
z ----> the amount of pineapple sent
we know that
so
-----> equation A
-----> equation B
-----> equation C
Part 1) Bottle 1
vanilla=?
almond=?
pineapple=4
we have
Find the value of x
substitute the value of z in equation B
Find the value of y
substitute the value of z in equation C
therefore
Bottle 1
vanilla=1
almond=3
pineapple=4
Part 2) Bottle 2
vanilla=?
almond=6
pineapple=?
we have
Find the value of x
substitute the value of y in equation A
Find the value of z
substitute the value of x in equation B
solve for z
therefore
Bottle 2
vanilla=2
almond=6
pineapple=8
Part 3) Bottle 3
vanilla=1 1/2
almond=?
pineapple=?
we have
convert to an improper fraction
Find the value of y
substitute the value of x in equation A
convert to mixed number
Find the value of z
substitute the value of x in equation B
therefore
Bottle 3
vanilla=1 1/2
almond=4 1/2
pineapple=6